2022
DOI: 10.1039/d1ta07910g
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom catalysts for thermal- and electro-catalytic hydrogenation reactions

Abstract: The review highlights recent advances and remaining challenges in single atom catalysts for thermal- and electro-catalytic hydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 143 publications
0
17
0
Order By: Relevance
“…Ni clusters are needed for the full hydrogenation of CO 2 with the 8e − redox cycle. 35 The unique characteristics of the SAC render Ni-SAC active for electro-chemical CO 2 reduction to CO. 154–157 Frei and his co-workers 35 confirmed that the MgO supported Ni-SAC is active for RWGS. MgO supported Ni NPs are normally highly active for CO 2 methanation.…”
Section: Co2 Hydrogenation To Comentioning
confidence: 88%
“…Ni clusters are needed for the full hydrogenation of CO 2 with the 8e − redox cycle. 35 The unique characteristics of the SAC render Ni-SAC active for electro-chemical CO 2 reduction to CO. 154–157 Frei and his co-workers 35 confirmed that the MgO supported Ni-SAC is active for RWGS. MgO supported Ni NPs are normally highly active for CO 2 methanation.…”
Section: Co2 Hydrogenation To Comentioning
confidence: 88%
“…[69][70][71] The uniformly distributed and separated active sites in SACs are highly similar to homogeneous catalysts, ensuring high metal availability compared to conventional nanoparticle catalysts. 72 This structural feature would be available for ECH. Zhang and co-workers proposed a simple fabrication for P-doped carbon-supported Cu catalysts with a high surface area and variable sizes of Cu sites, ranging from nanoparticles to single atoms.…”
Section: Nanostructured Cu Catalystsmentioning
confidence: 99%
“…145 In the following subsection, the application of ML for the establishment of structure–activity relationship, feature engineering, high-throughput screening, and stability of SACs is broadly discussed. As the application of SACs in thermal and electrochemical reactions was presented in a recent review paper, 158 we only focus on the progress of ML for the design of SACs and DACs especially for electrochemical reactions.…”
Section: Single Atom Catalysts (Sacs)mentioning
confidence: 99%